Quercetin 7-O-Glutamate Potentiates Staphylococcus aureus to Fluoroquinolone Antibiotics - Park, Kwang-Su; Choo, Hyunah; Kim, Mi Kyoung; Chong, Youhoon (WILEY-V C H VERLAG GMBH, 2016)
The quercetin conjugate Q-7-O-Glu (5) showed inhibition of NorA efflux pump and thereby potentiation of antibacterial activity of various antibiotics against S. aureus. In particular, upon combination with 5, the fluoroquinolone antibiotics (ciprofloxacin) showed 4-times enhanced antibacterial activity against S. aureus.
Keywords: MEDIATED MULTIDRUG-RESISTANCE; FLAVONOID DIMERS; BIVALENT MODULATORS; EFFLUX; NORA; INHIBITION; TRANSPORTER; MECHANISM